Civil Society di Masyarakat Muslim: Pengalaman Indonesia - Jamhari, Jamhari (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2000)
This book presents a study on democracy and civil society in non-Western countries. Like other discourse on democracy and modernization, civil society emerged in the West with its specific culture and tradition. Therefore the development of discourse on civil society in non-Western countries has raised a question: Is a social system that emerged in a particular culture compatible to a society with different culture and tradition? Among other things, the book edited by Robert W. Hefner is aimed to answer the above mentioned question. The contents of the book consists of two parts. The first part puts forward articles written by political scientists and sociologists on structure and basic frame of civil society, then the second part contains various articles written by anthropologists and sociologists on the development of civil society in various non-Western countries. Experiences of applying civil democracy in non-Western countries, as discussed in the second part of the book, shout that the discourse on democracy and civil society is not a simple matter.DOI: 10.15408/sdi.v7i2.713